2021
DOI: 10.1680/jbren.19.00018
|View full text |Cite
|
Sign up to set email alerts
|

The development of composite bridges with corrugated steel webs in China

Abstract: The prestressed concrete girder with corrugated steel webs is one of the most promising steel–concrete hybrid structures applied to highway and railway bridges, owing to its excellent mechanical properties and efficient material utilisation. Composite bridges with corrugated steel webs (CBCSWs) have undergone rapid development in China since 2005, resulting in remarkable technical progress in many aspects. A state-of-the-art review of CBCSWs in China is presented. Based on data collected for over 90 CBCSWs bui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Elkais et al [ 5 , 6 ] built a new equation to evaluate the ultimate shear strength of plate girders with CSWs based on numerical analysis and found that web thickness was the key factor affecting the shear capacity of the girders. In practice, composite beams with CSWs are prone to fatigue damage due to their complex constructional details under fatigue loads [ 7 ]. Li et al [ 8 ] found that the beams with CSWs showed excellent fatigue performance Zcompared to those with flat steel web, and stress concentration is prone to appear in the tension flange at the web-to-flange fillet weld toe [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Elkais et al [ 5 , 6 ] built a new equation to evaluate the ultimate shear strength of plate girders with CSWs based on numerical analysis and found that web thickness was the key factor affecting the shear capacity of the girders. In practice, composite beams with CSWs are prone to fatigue damage due to their complex constructional details under fatigue loads [ 7 ]. Li et al [ 8 ] found that the beams with CSWs showed excellent fatigue performance Zcompared to those with flat steel web, and stress concentration is prone to appear in the tension flange at the web-to-flange fillet weld toe [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, corrugated web girders were used in cable-stayed and extradosed bridges. Besides headed studs, perfobond-like and angled steel plates are often used as a shear connector, but in 1993, Hondani Bridge in Japan was built with embedded trapezoidal corrugated web, and cutouts with reinforcements were used for connection between steel and concrete (He et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Corrosion especially affects thin-walled structures, where small pitting corrosion placed in a susceptible place, or a small reduction in thickness may cause serious loss of capacity. A fine example of such structures are those with sinusoidally corrugated webs currently applied in girders (also arched ones [ 20 ]) and also composite structures, where the deck is made of concrete and the web of constructional steel [ 21 ].…”
Section: Introductionmentioning
confidence: 99%